Job stress and work-life balance on turnover intention: The mediating role of job satisfaction - Upadianti, Luh Putu Sutrisna; Surya, Ida Bagus Ketut (International research journal of management, IT and social sciences, 2025)
This study aims to examine the effect of Job Stress and work-life balance on turnover intention, with job satisfaction as a mediating variable among healthcare employees at RSU Grha Bhakti Medika in Bali. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from 92 nurses and midwives through a structured questionnaire. The results reveal that Job Stress has a positive and significant effect on turnover intention, while work-life balance and job satisfaction have negative and significant effects on turnover intention. Additionally, Job Stress negatively affects job satisfaction, whereas a good work-life balance positively influences job satisfaction. The mediation analysis confirms that job satisfaction partially mediates the relationship between job stress and work-life balance, as well as between work-life balance and turnover intention. These findings highlight the importance of reducing Job Stress and promoting work-life balance to enhance job satisfaction and lower turnover intention among hospital employees. The study offers practical implications for hospital management in developing HR policies that support employee well-being and retention, especially in the context of strengthening Indonesia’s health tourism sector.